Partisipasi Masyarakat Desa dalam Mendukung Pendidikan Anak Melalui Rumah Belajar di Desa Ononamolo Talafu Kecamatan Botomuzoi Kabupaten Nias - Mendrofa, Agung Rahmat Christin; Batubara, Beby Masitho; Angelia, Nina (Universitas Medan Area, 2025)
Education in Ononamolo Talafu Village has sufficient facilities, but the quality still needs attention. The main obstacles include limited internet access, lack of educators, and inadequate learning facilities. This study aims to identify the form of community participation in supporting children's education through learning homes and the obstacles faced in its implementation. This study uses the theory of Engkosworo and Komariah (2010:297), which categorizes community participation in education into two forms: financial contribution and contribution of thought and energy. The method used is qualitative with observation, interview, and documentation techniques. The results of the study show that the contribution of community financing supports the existence of a Learning House in Ononamolo Talafu Village in the form of providing cash, and goods needed for learning. This is followed by the contribution of the community's thoughts in the form of ideas in building children's learning enthusiasm by making children's handicrafts and displaying them on the walls of the learning house. Then the contribution of manpower can be seen that the community helps the process of building a learning house.